2004
DOI: 10.1037/0021-9010.89.5.835
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits and Individual Job Performance Growth Trajectories in Maintenance and Transitional Job Stages.

Abstract: This study extends the literature on personality and job performance through the use of random coefficient modeling to test the validity of the Big Five personality traits in predicting overall sales performance and sales performance trajectories--or systematic patterns of performance growth--in 2 samples of pharmaceutical sales representatives at maintenance and transitional job stages (K. R. Murphy, 1989). In the maintenance sample, conscientiousness and extraversion were positively associated with between-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
242
4
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(273 citation statements)
references
References 120 publications
(208 reference statements)
13
242
4
14
Order By: Relevance
“…Researchers have therefore frequently controlled for work characteristics when investigating recoveryrelated variables like psychological detachment (e.g., Fritz et al, 2010;Sonnentag, 2003). In order to be able to control for potential confounding effects, we therefore chose to control for workload and time pressure with a German translation of the Questionnaire on the Experience and Evaluation of Work (VBBA; van Veldhoven & Meijman, 1994; see also Bakker, Veldhoven, & Xanthooulou, 2010). The VBBA measures quantitative work demands in terms of workload and time pressure with 11 items.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have therefore frequently controlled for work characteristics when investigating recoveryrelated variables like psychological detachment (e.g., Fritz et al, 2010;Sonnentag, 2003). In order to be able to control for potential confounding effects, we therefore chose to control for workload and time pressure with a German translation of the Questionnaire on the Experience and Evaluation of Work (VBBA; van Veldhoven & Meijman, 1994; see also Bakker, Veldhoven, & Xanthooulou, 2010). The VBBA measures quantitative work demands in terms of workload and time pressure with 11 items.…”
Section: Methodsmentioning
confidence: 99%
“…To have an indication of the strength of effects, we calculated pseudo-R 2 statistics (Raudenbush & Bryk, 2002;Singer & Willett, 2003; see also Thoresen, Bradley, Bliese, & Thoresen, 2004). As can be seen from Table 5, the growth term weekday predicted 4% of within-person variation in psychological detachment, Level 2 work demands and trait mindfulness explained 22% of intercept variance (interindividual differences in participants' starting values in psychological detachment), and trait mindfulness explained about 53% of the variance in weekday slopes (interindividual differences in participants' change patterns in psychological detachment over the work week).…”
Section: Mindfulness and Change Trajectories In Psychological Detachmmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore investigated differences between the three groups in change of tips per client across the 10 days in a growth modeling analysis (Bliese & Ployhart, 2002). Training processes often follow a learning curve which can be characterized by a positive linear (sharp increase in the beginning), a negative quadratic, and a positive cubic trend (continued increase but at a slower rate) at the origin of time (Thoresen, Bradley, Bliese, & Thoresen, 2004). Growth modeling results revealed that changes in tip in the compliant intervention group between Day 1 and Day 10 were in line with a learning curve (linear: coef.…”
Section: Supplementary Analysesmentioning
confidence: 99%
“…[6][7][8] This instrument is available for the assessment of the five-factor model (FFM) that comprises the broad trait dimensions of openness to experience, conscientiousness, extraversion, agreeableness, neuroticism and their more specific facets as one of the most widely accepted taxonomic structures of personality. 10 This model provides a framework of informed personality research in organisational studies 11 due to its ability to predict the performance of individuals in different occupational settings 12 mostly because of the conscientiousness trait suggested as being the most consistent trait in predicting good work outcomes across different contexts.…”
Section: 3mentioning
confidence: 99%